Modulation of bulk heterojunction morphology through small π-bridge changes for polymer solar cells with enhanced performance. Issue 22 (24th May 2018) - Ma, Yunlong; Chen, Huipeng; Tang, Yabing; Wang, Jin-Yun; Ma, Wei; Zheng, Qingdong
Abstract : Polymer packing structures and bulk heterojunction morphology can be controlled by small π-bridge modulation. Abstract : Investigations on the relationships among the chemical structures, morphology and photovoltaic properties of conjugated polymers are crucial in designing high-efficiency semiconducting polymers. Here, two novel copolymers, PIBTO-T andPIBTO-TT, were designed and synthesized to demonstrate the improvement in photovoltaic performance of conjugated polymers by a small change in their chemical structures.PIBTO-TT with thieno[3, 2- b ]thiophene π-bridges has a more linear backbone conformation, thereby resulting in enhanced intermolecular π–π interactions compared toPIBTO-T with thiophene π-bridges. Benefiting from the closer intermolecular π–π stacking, PIBTO-TT :PC71 BM exhibits a higher hole mobility thanPIBTO-T :PC71 BM. Morphological studies reveal that the miscibility of PC71 BM inPIBTO-TT is better than that inPIBTO-T . This enhanced miscibility could shorten the distances between adjacent fullerenes and improve electron transportation in the miscible region. Meanwhile, PIBTO-TT :PC71 BM blends have larger donor/acceptor interfacial areas thanPIBTO-T :PC71 BM samples. All these factors contribute to the better photovoltaic performance ofPIBTO-TT -based devices. This study clearly shows that the morphological characteristics and photovoltaic properties of conjugated polymers are closely related to their molecular structures, and the manipulation of backbone conformation through π-bridge modulation is a promising molecular engineering approach to improve the photovoltaic properties of conjugated polymers.